SELEKSI AKADEMIK DALAM PEMILIHAN KEPALA DESA: ANTARA RASIONALITAS KEBIJAKAN DAN TANTANGAN DEMOKRASI LOKAL - Hidayat, Tofan (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
This study examines the implementation of the academic selection policy in village head elections and its implications for local democratic practices. The academic selection policy is implemented as an additional mechanism to improve the quality of village leadership, particularly when the number of prospective candidates exceeds the stipulated limit. This research employs a qualitative approach with a descriptive-analytical design and is grounded in the policy implementation model of Van Meter and Van Horn, which emphasizes key variables including policy communication, resources, implementers’ disposition, bureaucratic structure, and the socio-political environment. Data were collected through in-depth interviews, observation, and document analysis in Indramayu Regency and were analyzed using an interactive data analysis model consisting of data reduction, data display, and conclusion drawing. The findings indicate that, procedurally, the implementation of academic selection has complied with existing regulations; however, substantively, it has not been fully effective. The main challenges of the policy lie in weak policy communication, disparities in candidates’ educational backgrounds, and the conditional application of academic selection, which has generated perceptions of injustice and reduced democratic acceptance among village communities. The novelty of this study lies in positioning academic selection as a dilemma between policy rationality and local democracy, emphasizing that the success of policy implementation at the village level should be assessed not only through procedural compliance but also through the degree of democratic acceptance within society.